Analisis Kesiapan dan Tantangan Implementasi Zakat Core Principles (ZCP) dan Wakaf Core Principles (WCP) dalam Penguatan Pengelolaan Keuangan Sosial Islam di Indonesia - Betza Dona Marchanda; Mahfuzh Ihsan Alghifari; Muaafi Karnanda; Tiara Disinta Syafitri (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Islamic social finance through zakat and waqf instruments has significant potential to support economic development and improve social welfare in Indonesia. However, its management still faces challenges related to governance, transparency, accountability, and human resource capacity. This study aims to analyze the readiness and challenges of implementing Zakat Core Principles (ZCP) and Waqf Core Principles (WCP) in strengthening Islamic social finance management in Indonesia. This research employs a descriptive qualitative method with a library research approach, utilizing data from academic journals, books, regulations, and official documents related to zakat and waqf. The findings indicate that Indonesia has a relatively good level of readiness for implementing ZCP and WCP, supported by regulations, institutional frameworks, and the digitalization of zakat and waqf management. Nevertheless, several challenges remain, including low public literacy, limited human resource capacity, suboptimal use of digital technology, and the need for stronger governance and supervision systems. The implementation of ZCP and WCP plays a strategic role in enhancing transparency, accountability, and effectiveness in managing zakat funds and waqf assets, while strengthening the contribution of Islamic social finance to economic development and social welfare. Therefore, collaboration among government institutions, zakat and waqf management bodies, and society is essential to optimize the sustainable implementation of these principles.